ETNOMATEMATIKA: APLIKASI MATEMATIKA PADA PERHITUNGAN HARI SUCI AGAMA HINDU DAN BANTEN - Gede Ngurah Oka Diputra; I Wayan Sudiarta; Ni Made Serma Wati (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
Mathematics and culture are two interrelated things. Mathematics in culture is known as ethnomathematics. Ethnomathematical objects that are around us can be used to carry out mathematics learning. We can find mathematical concepts in a particular culture, for example in the calculation of Hindu religious holy days and the forms of offerings. Calculation of Hindu holy days Religious holidays for Balinese Hindus are generally calculated based on wewaran and pawukon with the application of the concept of the Corruption Eradication Commission. While in Banten, various forms of offerings are found in the form of flat shapes. The method used in this writing is a literature study, namely data collection techniques by conducting a review study of books, literatures, notes, and reports that have to do with the problem being solved.